Utilization of the Pediatric Modified Dynamic Gait Index: Issues Related to Child Development. (2nd November 2019) - Anderson, Deborah K.; Cech, Donna
Abstract: Aims: This cross-sectional study investigated how typically developing children performed on a version of the Dynamic Gait Index, modified for children (Pediatric Modified DGI). Methods: Seventy-four typically developing children, ages 7–18 years, were evaluated using the Pediatric Modified DGI. Scores were analyzed in three age groups using descriptive statistics for age-related performance. The Kruskal–Wallis and Mann–Whitney U tests were used to evaluate group differences. Results: Children performed differently on the Pediatric Modified DGI between the three groups (Kruskal–Wallis H (2) = 18.819, p < .05). Mann–Whitney U post hoc testing identified significant differences between the 7 to 10 and the 15 to 18-year-old groups ( U  = 128.5, p = .000, r = –.54) and between the 11 to 14 and the 15 to 18-year-old groups ( U  = 139, p = .001, r = –.46). Pediatric modified DGI scores were notably different between the three age groups on three of the items: horizontal head turn, vertical head turn, and pivot turn. Conclusions: Children's age appears to impact performance on the pediatric modified DGI, which should be considered when using this tool to examine functional mobility. Future studies should explore functional mobility assessments that consider sensory system development.